KORELASI ANTARA TINGKAT KEMAMPUAN BERPIKIR KREATIF DENGAN KOMPETENSI PENGETAHUAN IPS - Sari, Cintya Puspita (Journal for Lesson and Learning Studies, 2018)
This study aimed to determine the correlation between level of creative thinking ability with social knowledge competency of students of grade V in elementary school Gugus Kapten Kompyang Sujana in the lesson year 2017/2018. The type of this research was ex post facto. The method used in this research is descriptive method with correlation study type. Research populations were all students grade 5 in elementary school Gugus Kapten Kompyang Sujana academic period 2017/2018 which has population over 637 students. Sample was determined by proportional technique random sampling with the level of error 5% and the number of sample gained from the populations were 227 students. The data were obtained through the results of a creative thinking essay test which was answered by the respondents. The statistical analysis used in this research is hypothesis test using triserial correlation analysis. Based on the result of analysis then rptscount = 1,005. At a level of signification 5% with n = 227, then obtained rtable= 1,960. Because rcount= 1,005 >rtable= 1,960 it means that H0 that said there is no significant correlation between level of creative thinking ability with social knowledge competency of students of grade V in elementary school Gugus Kapten Kompyang Sujana in the lesson year 2017/2018 was accepted. The conclusion was there is no correlation between level of creative thinking ability with social knowledge competency of students of grade V elementary school Gugus Kapten Kompyang Sujana in the lesson year 2017/2018. Suggested to other researchers for the results of this study can be used as a reference to carry out further research using the test is a creative thinking essay test.Keywords: level of creative thinking ability, social knowledge competency, students of grade V elementary school.